Pengaruh Population Aging, Fertilitas, Dan Pendapatan Nasional Per Kapita Terhadap Emisi CO2 - Yusuf Amri (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2026)
The elderly population continues to grow, while birth rates tend to decline relatively in many countries. Energy consumption levels have increased along with the rising global population. This increase in energy consumption has led to higher CO2 emissions worldwide. Several studies have shown that the rising percentage of elderly individuals and the decline in the Total Fertility Rate (TFR) affect CO2 emissions. The objectives of this study is to examine the impact of the elderly population percentage and TFR on CO2 emissions and to determine whether national income per capita serves as a moderating variable in this relationship. The study employs the Moderation Regression Analysis (MRA) method, using data from the World Bank (2019) covering 225 countries. The findings indicate that, on a global scale, the percentage of elderly individuals and TFR significantly influence CO2 emissions. A 1% increase in the elderly population results in a 0.137 increase in CO2 emissions, while a 1% increase in TFR leads to a 0.702 increase in CO2 emissions. Furthermore, the effect of the elderly population percentage and TFR on CO2 emissions is moderated by national income per capita, with significance values of b2 (elderly) = 0.000; b3 (elderly) = 0.000 and b2 (TFR) = 0.000; b3 (TFR) = 0.004 (Quasi Predictor). Keywords : population aging, fertility, national income per capita, CO2 emission